Perancangan Eksperimen Proses Ekstrusi Dengan Bahan Plastik Bekas Pakai - Hanky Fransiscus, S.T., M.T.; Sugih Sudharma Tjandra; Monika Pangestu; Lusi Handranto (Universitas Katolik Parahyangan, 2022)
Today, plastic waste is a serious problem and needs to be resolved immediately. Indonesia is the second largest contributor of plastic waste to the sea after China. This condition needs to be resolved immediately by looking for alternative solutions for plastic waste in all areas of life, including plastic waste in educational institutions. Observations at the Parahyangan Catholic University (Unpar) show that 41% of the total inorganic waste come from plastic packaging bottles. One alternative solution to the plastic waste problem is to recycle plastic waste and process it into other products that can be used. One alternative that is being explored for the process of recycling plastic waste in the Unpar environment is to use an extrusion machine in the Production Process Laboratory of the Faculty of Industrial Technology (FTI) Unpar. However, this machine has never been used for recycling plastic waste to be made into other products and the process parameters that can produce a good product are not yet known. Therefore, in this study, experimental design was carried out to determine process parameters to produce a good product with the existing extrusion machine. The plastic waste used in this test is plastic waste from Polypropylene (PP) plastic and Polyethylene Terephthalate (PET) plastic. The research consist of determining factors, factor levels, and randomization of treatment using completely randomized design method. The response of this experimental test is the result of product quality assessment involving 3 experts. The results show that the extrusion process on PET plastic waste materials with existing machines has not produced good recycled products. Other processes and machine improvements are still needed to produce a good product. As for PP plastic waste material, the recycling results obtained are quite good. The ANOVA test results show that the barrel temperature will affect the value of the quality of the product produced from PP plastic waste.